Heat acclimatization - Armstrong, L. E. (Encyclopedia of Sports Medicine and Science, 1998)
The article deals with: - Physiological Responses, - Heat Illness, - Factors Affecting Acclimatization, - Loss of Acclimatization. It has been published in: Encyclopedia of Sports Medicine and Science, T.D.Fahey (Editor). Internet Society for Sport Science: http://sportsci.org. 10 March 1998.